Believing the lie [compact disc, unabridged] : an Inspector Lynley novel - George, Elizabeth, 1949- (George, Elizabeth, 1949- Inspector Lynley novel., 2012)
In this novel, Inspector Thomas Lynley is mystified when he's sent undercover to investigate the death of Ian Cresswell at the request of the man's uncle, the wealthy and influential Bernard Fairclough. The death has been ruled an accidental drowning, and nothing on the surface indicates otherwise. But when Lynley enlists the help of his friends Simon and Deborah St. James, the trio's digging soon reveals that the Fairclough clan is awash in secrets, lies, and motives.